VISUALIZATION OF MICROWAVE ABSORPTION OF THE GRAPHITE PERIODICAL STRUCTURE WITH THERMOELASTIC OPTICAL MICROSCOPE - Odabashyan, Levon A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2020)
This paper shows a non-destructive visualization of the absorption of microwave filed by a graphite periodic structure. The visualization system was a thermo-elastic optical indicator microscope. The article presents the interaction of the electromagnetic field with graphite cylindrical cells of periodicity and shows the distribution of the electromagnetic field over the graphite cells. Depending on the distance between the periodic structure of graphite and the microwave source, the electromagnetic field distribution and absorption rate were different. The visualization was performed using a microwave signal with a frequency of 11 GHz and a maximum power of 35 dBm.